2000
DOI: 10.1046/j.1524-475x.2000.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human platelet‐derived growth factor‐BB (becaplermin) for healing chronic lower extremity diabetic ulcers: an open‐label clinical evaluation of efficacy

Abstract: Topically applied recombinant human platelet-derived growth factor-BB (becaplermin) is a new pharmacologically active therapy for chronic, neuropathic, lower extremity diabetic ulcers. In previous studies, becaplermin gel was administered once daily but dressings were changed twice daily. In the present study of 134 patients with diabetes mellitus and full thickness lower extremity ulcers, dressings were changed only once per day, simplifying the treatment regimen. Efficacy criteria included the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 24 publications
1
83
0
3
Order By: Relevance
“…The acid tide of wound healing, i.e., the pH within wounds and fractures, change from acidic to neutral and alkaline pH as the healing process progress (18)(19)(20)(21)(22)(23)(24). The local environment is acidic during the initial stage of healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acid tide of wound healing, i.e., the pH within wounds and fractures, change from acidic to neutral and alkaline pH as the healing process progress (18)(19)(20)(21)(22)(23)(24). The local environment is acidic during the initial stage of healing.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, platelet-rich plasma (PRP), platelet lysates, platelet-derived growth factor (PDGF), and supernatants from activated platelets all have well-known stimulatory effects on mesenchymal cells in vitro (4-10) and in vivo (11). The clinical potential of platelet constituents is interesting and several clinical trials and observations on wound healing and bone formation have been published (12)(13)(14)(15)(16)(17)(18). Previously, it has also been described that mineralization and bone repair is pH dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In a large multicenter study, PDGF, at a concentration of 100 g/g in cream, gave a better healing rate (50%) than the placebo group (35%) in a 20-week study (P ϭ 0.007) (17). In an open-label study, Embil et al (19) reported a complete healing rate of 57.5%, with a daily local application of PDGF cream, in chronic diabetic foot ulcer patients. The wide healing ranges shown above probably reflect differences in study design, duration of study, and patient and ulcer characteristics.…”
Section: Hegf and Diabetic Foot Ulcersmentioning
confidence: 99%
“…Regranex (PDGF-BB), the first and only Food and Drug Administration-approved cytokine (protein) treatment for cutaneous wound repair, was used as a positive control in the wound healing experiments. 30,43,44 The percentage of epithelial resurfacing (percent re-epithelialized) with 5.0 mg/ml CRT (100 g/wound) was 58% compared to 41% and 44% for the PDGF-BB-treated and buffer-treated wounds, respectively, at 5 days after injury ( Figure 1A). As shown, by 10 days after wounding, the CRT-treated and control wounds were 100% re-epithelialized ( Figure 2, A, B, D, E).…”
Section: Crt Enhances Porcine Wound Healingmentioning
confidence: 99%